Communication with mothers of newborns under phototherapy: humanistic presupposition - Antonia do Carmo Soares Campos (Rev Rene)
The process of communication of the health team with the mother whose child is under phototherapy is fundamental so that she can calm down and become acquainted with the treatment. The thesis defended in this research is that the communication permeated by the Nursing humanistic care will contribute to the mother of the newborn under phototherapy come to know, understand the treatment and this way be well and be – better. We aimed to analyze the communication with mothers of newborns under phototherapy through the Phenomenological Nursing Process of the Paterson and Zderad’s Humanistic Theory. Qualitative, exploratory and descriptive study, instrumentalized through the mentioned process, in five stages: the preparation of the nurse to come to know; the nurse knows intuitively the other; the nurse knows scientifically the other; the nurse synthesizes in a complementary way the known realities; the internal succession of the nurse starting from many to an only paradoxical. It had as environment a public maternity hospital in Fortaleza-CE.